Social distancing as social engineering & health management: Applied ethics perspective to global management & strategic leadership - Nirbhay Kumar Mishra (Research in Globalization, 2020)
Resilient leadership and responsible attitude are the crucial factors for social-economic, engineering and management developments, and in the absence of those, a crisis usually takes place. The same happened in the case of Corona pandemic. Both China and WHO did not adequately manage the epidemic, and could not control; it turned ultimately in a pandemic. Asian Development Bank Report estimates global economic loss up to 8.8 trillion due to Covid-19. Undoubtedly, the Corona outbreak has severely affected SDGs and put forth several socio-economic-managerial challenges to sustainability and human development. The UN, World Bank, IMF, ADB, and ILO which prepare global social-economic strategies to reach the sustainability goals are working on the problem-solving mode to arrive at the best possible approach to get rid of the worst possible disease at present. Undoubtedly, reversing to a normal-healthy life is a difficult task. However, India is responding to the world's hopes, and motivating the leaders, policymakers, managers and technocrats to accept the new model of health management and medical leadership to contribute in developing the global narrative what we call the 'New-Normal'.
Keywords: 330; Covid-19; Engineering-management; Management & strategic leadership; Mathematical-modeling; Medical-ethics; New-Normal; Social-distancing